Improving donor support for governance: the case for more rigorous impact evaluation - Maria Melody Garcia (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
There is a broad consensus in the development community on the importance of governance both as a precondition for aid and as an essential aspect for social and economic development. Each year billions of dollars are spent on supporting interventions aimed at combating corruption, promoting democracy, strengthening state institutions, upholding human rights and preserving peace. Yet our knowledge of the effectiveness of these interventions remains very limited. Donors have made extensive use of outcome monitoring and cross-country analysis to demonstrate results in governance. Although these approaches can sketch out the progress of governance support, they do not provide convincing evidence that the observed outcome can be attributed to a given intervention alone. What is needed is a stronger approach – an approach that measures impact rather than monitoring outcome; an approach that attributes governance outcomes to the intervention by isolating other influential factors. Such an approach is generally known as rigorous impact evaluation. Donors have not adequately applied this approach to governance, unlike such `traditional' sectors as health, education and labour. For instance, research shows that only one of 165 US stabilisation interventions has been rigorously evaluated. Of the 800 or so completed and ongoing rigorous impact evaluations of development programmes in the last five years, only 10 per cent or less are estimated to be governance-related. This scenario is quite puzzling. Apart from the efficiency gains to be made from allocating scarce resources to interventions that work, conducting rigorous impact evaluation in governance is very important, given the unintended, yet potentially damaging consequences of an inappropriate governance intervention. Development cooperation in such fields as democracy, transparency and human rights, is too important, to base our knowledge purely on anecdotal evidence. Why, then, is there so little rigorous evaluation in this field? Rigorous governance evaluation poses three key challenges: Governance outcomes are difficult to quantify. Rigorous impact evaluation can capture no more than narrow aspects of complex, `system-wide'governance support and short-term impacts. A lack of incentive, since evaluation results may constrain political choices. Past evaluations provide valuable recommendations to tackle these challenges. In quantifying governance outcomes, use context-specific information or conduct behavioural games. In dealing with complex `system-wide' interventions, identify components of the programme that is viable for rigorous analysis. In improving incentives, persuade politicians to implement rigorous evaluations by studying the impact of their priority interventions and by setting appropriate expectations. Rigorous impact evaluation in governance is difficult but feasible. As donors face increasing pressure to demonstrate results, rigorous impact evaluations should work with, not against, achieving improved governance support and development outcomes.
Keywords: 330